BEFORE SCHENGEN – READY FOR SCHENGEN Euroregional Organisations and New Interregional Formations at the Eastern Borders of Hungary - Baranyi, Béla (Discussion Papers, 2012)
It’s more than fifteen years that European regional policy and regional sciences have shifted towards political borders, the issues of borderland and transboundary co-operation. Borderland issues, the research on the dividing and connective functions of borders has vital importance in the transitional countries of East Central Europe too. The political changes of the turn of the 1980s and 1990s opened new prospects in the Carpathian Basin as well. As the ‘iron-curtain’ disappeared the strict dividing role of state borders seemed to decrease and the prospect of cross-border relations seemed to broaden in the Carpathian Basin. But with new perspectives, the old problems of co-operation have also been preserved. Hungary’s European accession may offer an optimistic perspective for the future but the moving of Schengen borders to East Hungary may ‘drop a black shadow’ on improving Hungarian-Romanian and Hungarian-Ukrainian relations and worsen the situation of Hungarian ethnic minorities as well as inter-ethnic relations. All these verify the special scientific and national importance of preparation for the situation following the European accession.